Differential tissue and cellular distribution of chemokine C-C motif ligand 2 in grey/white matters of healthy and simian immunodeficiency virus infected monkey - Xue Shi; Jingdong Zhang; Huangying Zhao; Hongjun Li; Junyi Zhu; Huangui Xiong (Brain Research Bulletin)
Previous studies have shown that CCL2 concentration is higher in cerebrospinal fluid than in plasma of health and human immunodeficiency virus (HIV) infected individuals, suggesting an extra source of CCL2 in brain. Brain cellular CCL2 has been broadly studied in cultured cells and its in-vivo cellular distribution has been investigated in rodent experimental autoimmune encephalomyelitis model. However, its cellular distribution in grey and white matter (GM, WM) remains elusive. We explored this issue using healthy and simian immunodeficiency virus (SIV) infected monkeys and found: 1) Neurons were a major source of CCL2-like immunoreactivity (CCL2-ir) in normal GM, and corpus callosum (CC) ependyma showed high density of CCL2-ir. 2) Upon SIV infection, CCL2-ir was strikingly raised in GM neurons, and in CC ependyma. 3) Brain vascular-perivascular cells were a large source of CCL2-ir in normal GM and WM, which was relatively larger in CC WM than in GM. 4) Vascular-perivascular CCL2-ir proportional areas were significantly enhanced by SIV infection in both GM and CC WM. 5) Microglia seemed not to express CCL2 in healthy brain. Microglia-marker and CCL2-ir co-labeled cells were significantly increased by SIV infection. 6) A vast of macrophage-like cells were situated along infected CC ependyma, suggesting a large number of monocytes be crossing ependyma, which may be related to establishment of viral reservoir. In conclusion, our study provides valuable insights into the cellular sources and alterations of CCL2 in the monkey brain under normal and SIV-infected conditions, which may promote better understanding of CCL2 in related neurological processes.